Dampak Positif dan Negatif Penggunaan Aplikasi AI dalam Proses Pembelajaran Bahasa Indonesia di SMAN 1 Tungkal Jaya - Thalia Margaretaa; Okta Shelty; Hetilaniar Darwin; Darwin Effendi (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to describe the positive and negative impacts of using artificial intelligence (AI) applications such as ChatGPT, Grammarly, and Quillbot in the Indonesian language learning process at SMAN 1 Tungkal Jaya. This study used a qualitative descriptive method, with Indonesian language teachers as the primary subjects and 10th-grade students as additional informants. Data were collected through in-depth interviews, participant observation, and documentation, then analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results show that AI has a positive impact on teachers in the form of increased time efficiency, creativity in developing teaching materials, and innovation in digital learning. For students, AI increases motivation, facilitates access to information, and aids in understanding the material. However, negative impacts were also found, such as a decrease in the originality of teachers' ideas and pedagogical reflection, a reliance on machine-generated output, AI's limitations in understanding cultural contexts, and a decrease in critical thinking skills and an increase in plagiarism among students. Therefore, strengthening digital literacy and technological ethics is necessary so that the use of AI can become an effective, humanistic learning innovation that remains grounded in educational values.